2023
DOI: 10.13189/saj.2023.110105
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Plyometric Exercise, Strength Training on Physical Capabilities

Abstract: Objectives: The aim of this study is to compare a 10-week period, in which strength training (five weeks) was followed by plyometric training (five weeks) or the other way around among handball players. Hypothesis: Performing strength training first and then plyometric training will improve lower body strength and performance more than the reverse training sequence. Methods: Thirty-six young handball players voluntarily participated in this research. Pre and post test data (running, changing direction, jumping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 25 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…As said in the 'Study characteristics' section, there is a considerable disparity in the number of total ground contacts per session applied in the studies. Despite some studies recommending relatively low volumes of plyometric training (Ebben, 2007;Ebben, et al, 2014), and highlighting that higher volumes were not more effective than lower volumes, this systematic scoping review found one study (Alkasasbeh, 2023) that utilized as much as 600 ground contacts per session. However, it is important to note that this was the exception rather than the rule, since almost all the studies used less than 200 contacts per session, with the majority of them staying under 100 contacts per session.…”
Section: Number Of Total Contacts With the Surfacementioning
confidence: 86%
See 2 more Smart Citations
“…As said in the 'Study characteristics' section, there is a considerable disparity in the number of total ground contacts per session applied in the studies. Despite some studies recommending relatively low volumes of plyometric training (Ebben, 2007;Ebben, et al, 2014), and highlighting that higher volumes were not more effective than lower volumes, this systematic scoping review found one study (Alkasasbeh, 2023) that utilized as much as 600 ground contacts per session. However, it is important to note that this was the exception rather than the rule, since almost all the studies used less than 200 contacts per session, with the majority of them staying under 100 contacts per session.…”
Section: Number Of Total Contacts With the Surfacementioning
confidence: 86%
“…Two studies registered higher numbers, with one of them (Pancar, Biçer, & Ozdal, 2020) registering 200-300 contacts in most of the sessions, and the other (Alkasasbeh, 2023) registering more than 300 (up to 600).…”
Section: Number Of Total Contacts With the Surfacementioning
confidence: 98%
See 1 more Smart Citation
“…On the other hand, among the many sports that employ plyome tric training, we have handball where they seek to improve the performance of athletes through this method [31]. Some coaches have opted for ten-week programs where strength is trained during the first five weeks and the remaining five follow with plyometric training hoping that this sequence can be significantly improved in strength and lower body [32] as it is also expected that players can manage to develop better jumping skills [33]. Similarly, plyometric training programs are employed by rugby players [34].…”
Section: Introductionmentioning
confidence: 99%